An innovative approach to improve the teaching and learning in computer programming by using the web tutorial applications / Mohd Norafizal Abd Aziz, Mahfudzah Othman and Zainab Othman - Abd Aziz, Mohd Norafizal; Othman, Mahfudzah; Othman, Zainab (Universiti Teknologi MARA Cawangan Pahang, 2009)
Computer programming courses are often claimed to be tough and, thus, high failure rates usually becomes an issue debated over these years. Taking this issue into account, several methods and techniques have been incorporated by the lecturers in teaching programming courses in order to improve the success rates. This paper discusses the actors that influence the success and failure in programming courses, as well as the techniques and methods that have been already introduced by previous studies. This paper also discusses students' preferences and materials that they have been using to facilitate their learning Above all, the main intention of this study is to propose the use of web-based learning as an alternative tool that can be used in the teaching and learning programming Random sampling was used in this study and the respondents were students who enrolled in the Diploma in Computer Science programme in one of the public universities in Malaysia. The data collected were analysed using the SPSS software to determine the significance of using web-based tutorials in programming courses. The benefits of employing web-based learning in classes as result/rom research findings is discussed in the paper: It is hoped that lecturers will be aware of the effectiveness of thisapplication as it can help to improve their teaching and learning environment in programming classes.